2021
DOI: 10.1302/0301-620x.103b1.bjj-2020-1186.r2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of lumbar developmental spinal stenosis on back pain, radicular leg pain, and disability

Abstract: Aims To study the associations of lumbar developmental spinal stenosis (DSS) with low back pain (LBP), radicular leg pain, and disability. Methods This was a cross-sectional study of 2,206 subjects along with L1-S1 axial and sagittal MRI. Clinical and radiological information regarding their demographics, workload, smoking habits, anteroposterior (AP) vertebral canal diameter, spondylolisthesis, and MRI changes were evaluated. Mann-Whitney U tests and chi-squared tests were conducted to search for differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…Developmental lumbar spinal stenosis, for example, a condition with pre-existing short pedicles and a narrow bony spinal canal at many levels, was not assessed on MRI. 39 , 40 This study presents only radiological outcomes from the SSSS, as a complement to clinical results that are presented elsewhere. 8 The correlation between baseline parameters, two-year MRI findings, and two-year clinical outcomes will be evaluated in separate reports.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental lumbar spinal stenosis, for example, a condition with pre-existing short pedicles and a narrow bony spinal canal at many levels, was not assessed on MRI. 39 , 40 This study presents only radiological outcomes from the SSSS, as a complement to clinical results that are presented elsewhere. 8 The correlation between baseline parameters, two-year MRI findings, and two-year clinical outcomes will be evaluated in separate reports.…”
Section: Discussionmentioning
confidence: 99%
“…All families showed involvement of multilevel DSS in first‐degree relatives and in at least two generations, which suggests the entity as highly integrated between close relatives. Due to its relatively high prevalence of 7.3% in the population, 12 it is possible and reasonable that both parents being cases of multilevel DSS could marry each other as shown in Families 1–4. It is also important to note that the unaffected mother (2‐2) in Family 2 gave birth to at least 3 cases (50%) and 2 controls (33%), which may imply the father (2‐1) passing the disease gene to his offspring.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that the spinal canal should be studied in a three‐dimensional manner. The clinical implications of DSS should be addressed in future study 32,12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further limitation is the lack of detail about the presence of developmental stenosis that could be implicated in symptomatic adjacent level deterioration, which has been shown to be a risk factor for worse disability and poorer quality of life in a previous report. 19 Finally, the authors showed some fine examples of images, but does this represent usual care?…”
mentioning
confidence: 99%